Perancangan Interior Perpustakaan Kota Surabaya - Mariana Wibowo, Alfin Samuel (Intra, 2016)
In this modern era, Indonesia has a fairly low reading interest and left behind compared to Philippines, Malaysia and Singapore. Modern age demands make humans need to have extensive knowledge. The library is one of the centers of accurate and effective information, but most of the people today rely more on information and knowledge from the internet.Â  This is because the condition of the city library in Surabaya are uncomfortable and cant support reading activities. Therefore, in designing the interior of this library, the library is designed with homey design concept that has meaning simple, cozy and home-like atmosphere. There was also a facility to be made include the lobby, reception, book-lending area, adult and childrens reading area, display books, computer area and wireless internet (Wi-Fi), stationary area, the cashier area, an office area and a cafe. The designer believes by applying this design concept that has this advantages and facilities, this will increase interest in reading and make the library as a primary means of supporting the people reading activity, especially in Surabaya.